Intertextuality of God's Dialogue with the Prophet Moses in the Qur'an and the Torah: Analysis Perspective of Julia Kristeva - Nur Aeni Putri Gafar; Dian Nur Anna; Mar’atun Nabila (Lembaga Yasin AlSys, 2026)
This study examines the intertextuality of God’s dialogue with Moses in the Qur’an and the Torah through Julia Kristeva’s perspective. The research is motivated by narrative similarities between divine dialogue accounts in the two sacred texts, which indicate intertextual relations and meaning transformation. This study aims to identify the forms of intertextual relations between God’s dialogue with Moses in the Qur’an and the Torah and to reveal the processes through which meaning is transformed within these narratives. A qualitative library research approach was employed by analyzing Qur’an 20:11–14, Qur’an 4:164, Qur’an 7:143, and selected Torah passages, namely Exodus 3:1–6, Exodus 3:14, and Numbers 12:8. The analysis was conducted using Kristeva’s concepts of genotext and phenotext, supported by the principles of parallelism, transformation, modification, haplology, and demythification. The findings indicate that the Qur’an has a close intertextual relationship with the Torah as a genotext, yet this relationship is transformational rather than reproductive. The Qur’an preserves the narrative pattern of divine dialogue while simplifying symbols, adapting meanings, and affirming monotheism and divine transcendence within an Islamic theological framework. This study contributes to Qur’anic studies and intertextual literary analysis by demonstrating how sacred-text narratives can be examined through Kristeva’s theory to clarify continuity, transformation, and theological reinterpretation across religious traditions.